2012
DOI: 10.11139/cj.29.2.249-268
|View full text |Cite
|
Sign up to set email alerts
|

Wiki and Digital Video Use in Strategic Interaction - based Experiential EFL Learning

Abstract: This paper details the use of a free and access-controlled wiki as the learning management system for a four-week teaching module designed to improve the oral communication skills of Japanese university EFL students. Students engaged in repeated experiential learning cycles of planning, doing, observing, and evaluating their performance of a role in a strategic interaction scenario. Each performance was digitally video recorded and uploaded to the wiki. Students then used the wiki to evaluate their video perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Firstly, we stated that online teaching through wikis environments has a positive effect on teaching and familiarizing students with Italian language and culture. Researchers (Reinhardt, 2019;DeHaan et al, 2012;Tyrou & Mikros, 2012;Elola & Oskoz, 2010b) have focused on social and cultural qualities of formal online language use and interaction, such as computer-mediated collaborative learning (Warschauer & Kern, 2000), intercultural communication, situated learning, and self-presentation (Lam, 2000). By integrating authentic and up-to-date material in university departments that teach foreign language and culture, the language can be supported by the prevailing general framework and the required range of communication and sociolinguistic skills can be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, we stated that online teaching through wikis environments has a positive effect on teaching and familiarizing students with Italian language and culture. Researchers (Reinhardt, 2019;DeHaan et al, 2012;Tyrou & Mikros, 2012;Elola & Oskoz, 2010b) have focused on social and cultural qualities of formal online language use and interaction, such as computer-mediated collaborative learning (Warschauer & Kern, 2000), intercultural communication, situated learning, and self-presentation (Lam, 2000). By integrating authentic and up-to-date material in university departments that teach foreign language and culture, the language can be supported by the prevailing general framework and the required range of communication and sociolinguistic skills can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have looked at wiki-mediated co-writing L2 and concluded that wikis engage learners in the writing process by helping each other reorganize content and correct mistakes (e.g., Aydin & Yildiz, 2014;DeHaan et al, 2012;Kost, 2011;Elola & Oskoz, 2010;Kessler & Bikowski, 2010;Lee, 2010;Oskoz & Elola, 2010;Parker & Chao, 2007). Forte and Bruckman (2006) presented the writing-to-learn paradigm and the students' engagement in collaborative writing activities; in their research, they suggested that collaborative publishing on a wiki provide a fascinating model for creating authentic classroom writing activities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be potential when students understand themselves as their own wiki audience (cf. deHaan et al 2012, §3.1.3). For example, Pellet (2012) had 30 advanced French sociolinguistics undergraduate students create wikis to build, manage, and share course content knowledge—in French, directed by the students, without focus on grammatical accuracy (perhaps taking Kessler 2009, §3.1.1 into account).…”
Section: Wikismentioning
confidence: 92%
“…Because wikis are easily customizable, they can be used as VLEs that provide supplemental resources and scaffolding on how and why to use wikis for L2 learning. For example, deHaan et al (2012) had 13 university-level English learners in Japan use a wiki to prepare, transcribe, discuss, and practice spoken role plays, focusing on interactional competence and fluency. The researchers report overall improvements in grammar, pragmatics, vocabulary, and learner confidence.…”
Section: Wikismentioning
confidence: 99%